2016
DOI: 10.1080/09638237.2016.1207231
|View full text |Cite
|
Sign up to set email alerts
|

Use of the word schizophrenia in Portuguese newspapers

Abstract: Our results suggest the media has an active role promoting stigma, as well as passively broadcasting and thus passing on prejudices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…The disproportionate proportion of stigmatising coverage associated with schizophrenia could be for several reasons. Schizophrenia is frequently associated with violence and criminality when discussed in newspapers (Clement and Foster, 2008; Goulden et al ., 2011; Aoki et al ., 2016; Rodrigues-Silva et al ., 2017; Gwarjanski and Parrott, 2018; Bowen et al ., 2019), either in a metaphorical or literal sense. Newspapers focus on criminality and mission to report topics that are ‘newsworthy’ may create a selection bias towards only publishing stories about people with schizophrenia that have committed a criminal act.…”
Section: Discussionmentioning
confidence: 99%
“…The disproportionate proportion of stigmatising coverage associated with schizophrenia could be for several reasons. Schizophrenia is frequently associated with violence and criminality when discussed in newspapers (Clement and Foster, 2008; Goulden et al ., 2011; Aoki et al ., 2016; Rodrigues-Silva et al ., 2017; Gwarjanski and Parrott, 2018; Bowen et al ., 2019), either in a metaphorical or literal sense. Newspapers focus on criminality and mission to report topics that are ‘newsworthy’ may create a selection bias towards only publishing stories about people with schizophrenia that have committed a criminal act.…”
Section: Discussionmentioning
confidence: 99%
“…These results should be interpreted in the context of research discussed in the introduction indicating that media coverage of mental illness tends to disproportionately focus on crime and violence (Murphy et al, 2013;Rodrigues-Silva et al, 2017;Thornicroft et al, 2013). Indeed, a study of mental illness coverage in Canadian newspapers found that only 10% of Canadian newspaper stories focused on recovery, while 51% focused on crime, violence and danger in 2015 (Whitley & Wang, 2017a).…”
Section: Discussionmentioning
confidence: 74%
“…Evidence suggests that mainstream media coverage of mental illness tends to disproportionately focus on factors such as danger, criminality and violence (Murphy, Fatoye, & Wibberley, 2013;Rodrigues-Silva et al, 2017;Thornicroft et al, 2013). This can contribute to negative public attitudes, inaccurate beliefs and erroneous stereotypes about people with mental illness, often leading to prejudice and discrimination (McGinty, Webster, & Barry, 2013;Reavley, Jorm, & Morgan, 2016;Thornicroft, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This study replicated the method used by Rodrigues-Silva et al (2017) with some adaptations. The study used a cross-sectional design to explore the context surrounding mental health conditions in print media in India.…”
Section: Methodsmentioning
confidence: 73%